Why does the undergraduate education in Ecuador fall short to train skills for rural health? A qualitative study - Galo Sánchez del Hierro; Roy Remmen; Susana Alvear Durán; Paul Van Royen; Kristin Hendrickx (Fundación Salud y Desarrollo Andino, Saludesa Ecuador, 2018)
Background and Objectives Since 1970, Ecuador establishes mandatory rural health service as a requirement for licensing work. Medical education is based in the hospital with little contact with rural areas. There is little information on the training and skills needs of recent graduated doctors. The research focuses on the perceptions of rural doctors on obstetric skills needed in rural areas. The aim of our study was to describe how the basic doctor in rural areas addresses training and teaching in obstetric skills needed in rural areas during undergraduate medical education. Methods A qualitative research project was performed using focus group discussions involving 23 rural doctors who work in rural and marginal urban areas in Southern Ecuador.Â We identified themes that came from the data collected in the focus group and we selected those which are of interest for the readers in a detailed analysis. Rural doctors responded the following question: How do you feel with obstetric skills training at the University where you studied?Â Results The majority of participants describe two predominant themes: the undergraduate theoretical teaching process of obstetrical skills and the practice experiences during the clinical attachment. Not all required skills are taught and internalize during undergraduate rotations including internship. Discussion There is no definition of the recent graduate profile that determines a standard for medical education. Rural doctors expressed lack of knowledge and practice for the obstetrical skills that they were required to perform. There is an urgent need to identify a baseline undergraduate curriculum that meets the country needs.